Knowledge and practice of schoolteachers towards students with epilepsy in Khamis Mushate, Southern Saudi Arabia - Jobran M Alqahtani (Wolters Kluwer Medknow Publications, 2015)
Objectives: Epilepsy is a very common chronic neurological disorder in children throughout the world. This study was conducted to assess Saudi male schoolteachers' knowledge of epilepsy and practice in Southern Saudi Arabia. Subjects and Methods: A cross-sectional descriptive study was conducted among male teachers; 315 teachers filled a well-designed and pretested self administered questionnaire. Results: Approximately three-quarters (72.7%) of the schoolteachers had witnessed epileptic fits. Forty-six percent believed that epilepsy was caused by electrical discharges. Most of the school teachers (79.7%) disagreed with the idea of teaching children with epilepsy separately, or preventing them from sporting activity (50.5%). In addition, 94.9% disagreed with the idea that epilepsy was shameful. Unfortunately, 64.1% of the teachers who were exposed to cases of seizures were not able to provide first aid to students having epileptic fits (P = 0.03). Conclusions: The schoolteachers were generally knowledgeable about epilepsy. This fact can be used to design a national program through which teachers can help to bring about a well-informed and tolerant community toward epileptics.